The order of public reason : a theory of freedom and morality in a diverse and bounded world - Gaus, Gerald F. (New York : Cambridge University Press, 2011)
"In this innovative and important work, Gerald Gaus advances a revised, and more realistic, account of public reason liberalism, showing how, in the midst of fundamental disagreement about values and moral beliefs, we can achieve a moral and political order that treats all as free and equal moral persons. The first part of this work analyzes social morality as a system of authoritative moral rules. Drawing on an earlier generation of moral philosophers such as Kurt Baier and Peter Strawson as well as current work in the social sciences, Gaus argues that our social morality is an evolved social fact, which is the necessary foundation of a mutually beneficial social order. The second part considers how this system of social moral authority can be justified to all moral persons. Drawing on the tools of game theory, social choice theory, experimental psychology, and evolutionary theory, Gaus shows how a free society can secure a moral equilibrium that is endorsed by all, and how a just state respects, and develops, such an equilibrium"--Provided by publisher.
The fundamental problem -- Part I. Social Order and Social Morality: The failure of instrumentalism; Social morality as the sphere of rules; Emotion and reason in social morality -- Part II. Real Public Reason: The justificatory problem and the deliberative model; The rights of the moderns; Moral equilibrium and moral freedom; The moral and political orders -- Appendix A: The plurality of morality -- Appendix B. Economic freedom in states that best protect civil rights.
Includes bibliographical references (p. 561-589) and index.
Keywords: Political ethics